Feasibility of the use of financial board games as an educational aid. - Ngo, Siew Yean. (2008)
This study is a quantitative look at the feasibility of using financial board game as an education aid in introducing financial concepts to the students. Financial literacy has been increasingly noted by the society recently. With such interest generated, this study aims to find out methods in which financial education can be incorporated into the school curriculum.